2009
DOI: 10.1002/ajim.20746
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing hospital discharge data (HD) to compare fatal and non‐fatal work‐related injuries among Hispanic workers in New Jersey

Abstract: HD data are effective for monitoring trends over time across ethnic groups and injury types. Therefore, non-fatal injury surveillance should be considered for targeting specific worker populations for interventions to reduce exposure to workplace hazards, and can be a valuable surveillance tool in efforts to reduce occupational injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Asians suffering a work-related injury had a decreased likelihood of admission, OR 0.78 (95% CI 0.63-0.97), when compared to Whites. We also found that males had twice the likelihood of admission, which corroborates findings of McGreevy et al, who reported that Hispanic males in New Jersey had higher rates of hospital admission from work-related falls, motor vehicle accidents, machinery-related accidents, and blunt trauma (14).…”
Section: Discussionsupporting
confidence: 81%
“…Asians suffering a work-related injury had a decreased likelihood of admission, OR 0.78 (95% CI 0.63-0.97), when compared to Whites. We also found that males had twice the likelihood of admission, which corroborates findings of McGreevy et al, who reported that Hispanic males in New Jersey had higher rates of hospital admission from work-related falls, motor vehicle accidents, machinery-related accidents, and blunt trauma (14).…”
Section: Discussionsupporting
confidence: 81%
“…Studies based on data from the National Electronic Injury Surveillance System (NEISS‐Work) also did not find evidence of substantial downward trends in injury rates between 1996 and 2005 [Centers for Disease Control and Prevention, ; Shishlov et al, ]. Yet several studies and a multi‐state occupational injury surveillance system have reported declining trends in work‐related hospitalizations, using WC as payer to identify work‐related injuries [Council of State and Territorial Epidemiologists (CSTE); Dembe et al, ; McGreevy et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Medical chart data [Struttmann and Reed, 2002;Franklin and Davies, 2003;Greenlee et al, 2005;Earle-Richardson et al, 2008] and ambulance reports [Forst and Erskine, 2009] have been used for farm injury research; while hospital discharge data have been used in other, related fields [Alamgir et al, 2006;McKenzie et al, 2009;McGreevy et al, 2010]. The only published studies pertaining to the utilization of both ambulance reports and hospital discharge data was research studying the effectiveness of medical response [Grossman et al, 1995;Blackwell et al, 2009], and was not used for epidemiologic purposes.…”
Section: Introductionmentioning
confidence: 99%